Effectiveness of ultraviolet disinfection in reducing hospital-acquired Clostridium difficile and vancomycin-resistant Enterococcus on a bone marrow transplant unit. (18th September 2018) - Brite, Jennifer; McMillen, Tracy; Robilotti, Elizabeth; Sun, Janet; Chow, Hoi Yan; Stell, Frederic; Seo, Susan K.; McKenna, Donna; Eagan, Janet; Montecalvo, Marisa; Chen, Donald; Sepkowitz, Kent; et al.
Abstract: Objective: To determine the effectiveness of ultraviolet (UV) environmental disinfection system on rates of hospital-acquired vancomycin-resistant enterococcus (VRE) and Clostridium difficile . Design: Using active surveillance and an interrupted time-series design, hospital-acquired acquisition of VRE and C. difficile on a bone marrow transplant (BMT) unit were examined before and after implementation of terminal disinfection with UV on all rooms regardless of isolation status of patients. The main outcomes were hospital-based acquisition measured through (1) active surveillance: admission, weekly, and discharge screening for VRE and toxigenic C. difficile (TCD) and (2) clinical surveillance: incidence of VRE and CDI on the unit. Setting: Bone marrow transplant unit at a tertiary-care cancer center. Participants: Stem cell transplant (SCT) recipients. Intervention: Terminal disinfection of all rooms with UV regardless of isolation status of patients. Results: During the 20-month study period, 579 patients had 704 admissions to the BMT unit, and 2, 160 surveillance tests were performed. No change in level or trend in the incidence of VRE (trend incidence rate ratio [IRR], 0.96; 95% confidence interval [CI], 0.81–1.14; level IRR, 1.34; 95% CI, 0.37–1.18) or C. difficile (trend IRR, 1.08; 95% CI, 0.89–1.31; level IRR, 0.51; 95% CI, 0.13–2.11) was observed after the intervention. Conclusions: Utilization of UV disinfection to supplement routine terminal cleaning of rooms was not effective in reducing hospital-acquired VRE and C. difficile among SCT recipients.